Prophet Sulaymān Visiting Multiple Wives in a Single Night: A study of Ḥadīth Narration and its Responses - Ahmad Nabil Amir; Zunaidah Mohd Marzuki (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
The ḥadīth on “Prophet Sulaymān Visiting Multiple Wives in A Single Night” has been given as an example of a contradiction between ḥadīth and logic. It tells the story of Prophet Sulaymān sleeping with an enormous number of wives in a single night. Being portrayed as carrying erotic message, the ḥadīth has also been deduced as an example of forgery committed by the ḥadīth scholars themselves. This study aims to clarify the problematic allegations, deduce a number of responses and compare the ideas from significant finding in Jewish and Christian sources. It suggests that such problematic ḥadīth implicitly implying a form of muʿjizāt and karāmah in such tradition. The data provided from the nine canonical ḥadīth books, traditional commentaries (sharh), Biblical sources and related articles. The data analysed in a descriptive and analytical manner using qualitative and quantitative method. The study concludes that the ḥadīth fulfils the criteria of a rigorously authenticated ḥadīth given its inclusion in the canonical works of hadith and corroborated in other tradition and highly established in ḥadīth narrations. Hence, the claim of fabrication was categorically dismissed; the number of wives should be understood in general as indicating numerous wives while, ignoring the particular numbers. The study implicitly shows that the paragraph “single night” alluded to the narrative of muʿjizāt.